Markers of neutrophil activation and some immune and haematological indices in malaria infection during pregnancy - Rebecca Chinyelu Chukwuanukwu; Chioma Esther Agu; Alfred Ehiaghe; Dorothy Ezeagwuna; Martin Herrmann; Gerald Udigwe (BMC Immunology)
Abstract Background Neutrophils are the first responders to pathogen invasion and are important first-line defenders. The defence mechanism of activated neutrophils includes neutrophil extracellular traps (NETs) formation that immobilize pathogens, stop their spread within the tissues, and ultimately kill them. However, their roles in the context of malaria during pregnancy are still elusive. This study was conducted to investigate markers of neutrophil activation as well as immunological and haematological cellular responses during Plasmodium infection in pregnancy. Method A total of 340 pregnant women aged between 19 and 42 years were recruited for this study carried out in South-east, Nigeria. All the subjects were tested for malaria parasite (MP) status. Those infected with human immunodeficiency virus (HIV) and those with any other co-morbidity were excluded from the study. A total of 45 (13.2%) of the 340 pregnant women were positive for malaria. To assess immune, haematologic and NETs markers in the MP positive group, 45 matched malaria-negative pregnant women from the malaria negative group served as controls. Thus, the final study population was grouped into two categories: 45 pregnant women infected with Plasmodium falciparum and 45 pregnant malaria-negative control group. The neutrophil elastase concentration, myeloperoxidase activity, total white blood cell counts, white blood cell differential counts, platelet counts and haematocrit were assessed via standard laboratory methods. Results Findings from this study revealed lower levels of myeloperoxidase in the malaria- infected cohort (p = 0.013) than in the malaria negative cohort. The neutrophil elastase levels were also lower in the malaria negative group (p = 0.042). The total white blood cells, platelet and neutrophil counts were lower (p = 0.046, 0.012 and 0.015, respectively) in the malaria infected group when compared to the controls. Conversely, lymphocyte counts were higher in the malaria-infected group (p = 0.003). No cases with high parasitaemia were encountered among the pregnant women infected with Plasmodium falciparum. Conclusion Malaria infection led to alterations in immune and haematological parameters in this group, with mild and moderate malaria parasitaemia in the study cohort. Although there were some significant differences, the assessed values remained mostly within the normal range. Further studies in a larger cohort assessing pregnant women infected with placental malaria and those with fatal outcomes are important to further investigate the role of NETs in malaria infection.